HIV mortality and infection in India: estimates from nationally representative mortality survey of 1.1 million homes. (23rd February 2010) - Jha, Prabhat; Kumar, Rajesh; Khera, Ajay; Bhattacharya, Madhulekha; Arora, Paul; Gajalakshmi, Vendhan; Bhatia, Prakash; Kam, Derek; Bassani, Diego G; Sullivan, Ashleigh; Suraweera, Wilson; McLaughlin, Catherine; et al.
Abstract : Objective To determine the rates of death and infection from HIV in India. Design Nationally representative survey of deaths. Setting 1.1 million homes in India. Population 123 000 deaths at all ages from 2001 to 2003. Main outcome measures HIV mortality and infection. Results HIV accounted for 8.1% (99% confidence interval 5.0% to 11.2%) of all deaths among adults aged 25-34 years. In this age group, about 40% of deaths from HIV were due to AIDS, 26% were due to tuberculosis, and the rest were attributable to other causes. Nationally, HIV infection accounted for about 100 000 (59 000 to 140 000) deaths or 3.2% (1.9% to 4.6%) of all deaths among people aged 15-59 years. Deaths from HIV were concentrated in the states and districts with higher HIV prevalence and in men. The mortality results imply an HIV prevalence at age 15-49 years of 0.26% (0.13% to 0.39%) in 2004, comparable to results from a 2005/6 household survey that tested for HIV (0.28%). Collectively, these data suggest that India had about 1.4-1.6 million HIV infected adults aged 15-49 years in 2004-6, about 40% lower than the official estimate of 2.3 million for 2006. All cause mortality increased in men aged 25-34 years between 1997 and 2002 in the states with higher HIV prevalence but declined after that. HIV prevalence in young pregnant women, a proxy measure of incidence in the general population, fell between 2000 and 2007. Thus, HIV mortality and prevalence may have fallen further since our study. Conclusion HIV attributable death and infection in India is substantial, although it is lower than previously estimated.